MANAJEMEN PENGELOLAAN KEUANGAN KELUARGA BAGI IBU HAMIL - Puspita Sari, Selly; Intansari, Fixi; Sekar Larasati, Bayu; Mulyono, Andi; Ratnasari, Ratnasari; Sutinah, Sutinah; Fitria Inayah, Rhala (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2023)
The aim of this community service activity is to increase mothers' knowledge and understanding in managing finances in order to improve children's health and nutritional status, so that mothers can provide good and appropriate care for the child's growth and development process. This socialization was carried out on September 15 2023 at the village hall in Pekon Blitarejo, Gading Rejo District, Pringsewu Regency, Lampung Province. In general, the steps for Community Service activities can be divided into three stages, namely needs analysis, activity implementation, and evaluation. The results of this community service activity are that mothers can understand the importance of financial planning for the family. It is important to manage family finances, especially for pregnant women, so that nutritional needs are met in order to prevent stunting for pregnant women and babies born. Several ways that can be used to manage finances for the needs of pregnant women include detailing every need for food and drinks that are nutritious but affordable with the money they have. By providing nutritious food and drinks for pregnant women, it is hoped that the growth of the fetus in the womb will also provide adequate nutritional intake, thereby preventing stunting. Keywords: Financial Management, Pregnant Women, Stunting.